Does anticipatory psychological contract impact intent to join in Indian IT sector?. (2019) - ,; Prasad, Asha
The purpose for this paper is to determine the impact of anticipatory psychological contract (APC) on final intent of the candidate to join an organisation. A structured questionnaire has been developed by adopting the statements from the previous studies conducted in western context on APC and ITJ which has been used as an instrument to collect data from final year students of B.Tech and MCA studying in Central, State and Deemed Universities of Delhi. Exploratory and confirmatory factor analysis (CFA) was applied on APC followed by structured equation modelling to analyse the impact of each aspect of APC on ITJ. The three dimensions of APC were explored and confirmed as relational aspect, career aspect and transactional aspect. Career aspect and transactional aspect were found to be significant contributor to ITJ whereas relational aspect was found to be insignificant in the tested relationship.